Hikari Cafe / Ikmal Hijjaz Ikmal Hisham ... [et al.] - Ikmal Hisham, Ikmal Hijjaz; Nazemi, Muhammad Mustaqim; Basharuddin, Ahmad Izzani; Muhamad Radzuan, Muhamad Taufiq; Muhammad Shazerain, Muhammad Syukran Nasri; Abdul Khir, Ahmad Hafizi Izzuddin (2025)
Hikari Cafe is a contemporary cafe inspired by Japanese culture, offering a unique combination of premium pastries, specialty coffee, and savoury food. Established with the vision of bringing the authentic taste of Japanese pastries to a modern cafe setting, Hikari Cafe aims to provide customers with a cozy and inviting space to enjoy quality food and beverages. Our menu is centered around handcrafted Japanese pastries, such as creampuffs and mochibased treats, paired with expertly brewed coffee and a selection of comfort food options. Using only the finest ingredients and traditional techniques, we deliver a dining experience that blends authenticity with innovation. The cafe is designed to embody elegance and warmth, creating a serene environment that appeals to both individuals and families seeking relaxation or a place to connect. Hikari Cafe operates with a customer-focused approach, offering dine-in, takeaway, and online delivery services to cater to diverse preferences. Our financial strategy is structured to achieve profitability within the first year, supported by strategic marketing campaigns and seasonal promotions to attract new customers and retain loyal patrons. With a commitment to quality, creativity, and customer satisfaction, Hikari Cafe aims to become a leading name in the cafe industry, setting itself apart by offering a truly unique and memorable experience inspired by the art of Japanese pastries and cafe culture.